Kajian Upaya Pengendalian Penggunaan Tanah Di Kabupaten Temanggung Provinsi Jawa Tengah - Slamet Muryono (BHUMI: Jurnal Agraria dan Pertanahan, 2016)
ABSTRACT Limitations of the existence of natural resources, especially land, is increasingly felt both by the government as the manager of the land and the community as users of the land. Not only due to the increasing number of residents, but its speed of development is always in need of land to make the land users isincreasingly competitive. The object of the research is the use of land at the sites. LANDUSE is further correlated with the RTRW and LP2B for licensing the use of land in order to control the use of land. Instruments used in controlling the use of land consisting of Land Use Map (PT), Map of Spatial Plan (RTRW), and Sustainable Agricultural Land Map (LP2B). Conformity between the land use control instruments can be explained that the PT map with RTRW map, 77.58% rate of compliance in accordance with RTRW and 21.87% mismatch, while 0.55% of roads and rivers fit between PT and RTRW. Among LP2B map with PT map, 75.55% level of compliance in accordance with the LP2B direction, and mismatch much as 24.45%. Among RTRW map with LP2B map, compliance level is 89.45% in accordance with the LP2B direction, and 10.55% is not available.